Exploring Students’ Experiences in Learning Speaking through Task-Based Language Teaching: A Case Study in a Vocational High School - Lestari, Sekar Dwi; Mobit, Mobit; Samsi, Yogi Setia (Journal of Educational Sciences, 2025)
This study explores vocational high school students’ experiences in learning English speaking through Task-Based Language Teaching (TBLT). Many students face difficulties in speaking due to limited practice, anxiety, and fear of making mistakes. The research aimed to understand their feelings, challenges, and reflections during TBLT-based speaking lessons. A qualitative case study design was used, involving six tenth-grade students selected purposively based on their speaking levels (low, medium, high) as recommended by their English teacher. Data were collected through classroom observation and interviews, and analyzed using thematic analysis. The results showed that students had mostly positive experiences. They enjoyed practical tasks and peer interaction, which reduced anxiety and built confidence. However, they also struggled with vocabulary, pronunciation, and grammar, especially without clear instructions. Students suggested that tasks should be more relevant to their majors. Teachers are advised to design clearer, more contextual tasks and provide support in language use to optimize TBLT outcomes.